Distribution of Inheritance Regarding Child Adoption (Adoption) in Islamic Inheritance and Civil Law - Hadiansyah, Andi Fakhrizal Irsam; Nuryasinta, Radhityas Kharisma (Universitas Negeri Gorontalo, 2025)
The distribution of inheritance for adopted children in Islamic inheritance and civil law in Indonesia is a complex and multidimensional issue, reflecting the dynamics between the principles of religious law and the development of modern secular law. This study aims to analyze the position of adopted children in the Islamic inheritance system and civil law, and to identify the challenges and integrative solutions needed to protect their rights. The method used is qualitative with a descriptive-analytical approach, through literature studies, interviews with legal experts, and analysis of relevant laws and regulations. The results of the study indicate that traditional Islamic law does not automatically recognize adopted children as heirs, except through special mechanisms such as wills, while civil law provides greater flexibility by recognizing the inheritance rights of adopted children as equal to biological children. This difference gives rise to legal conflicts, especially in families that integrate the two legal systems. In addition to legal aspects, social and ethical factors such as cultural stigma also influence the acceptance of adopted children's inheritance rights. This study recommends harmonization between Islamic law and civil law through legal reform and constructive dialogue between stakeholders, as well as increasing education and public awareness regarding the rights of adopted children in inheritance. Thus, it is hoped that a more just and inclusive legal system will be created, which is able to protect the rights of adopted children while maintaining the basic principles of Islamic law.